2023
DOI: 10.1101/2023.03.14.532655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CTLA-4 tail fusion enhances CAR-T anti-tumor immunity

Abstract: Chimeric antigen receptor (CAR) T cells are powerful therapeutics; however, their efficacy is often hindered by critical hurdles. Here, utilizing the endocytic feature of the cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) cytoplasmic tail (CT), we reprogram CAR function and substantially enhance CAR-T efficacy in vivo. CAR-T cells with monomeric, duplex, or triplex CTLA-4 CTs (CCTs) fused to the C-terminus of CAR exhibit a progressive increase in cytotoxicity under repeated stimulation, accompanied by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…CTLA4, recognized as an inhibitory receptor on T cells, when embedded in the CAR signaling architecture resulted in potent CARs capable of promoting a robust T cell response, particularly amongst the CD4 compartment, with a persistent cytotoxic phenotype. Despite the inhibitory effect of CTLA4 signaling ( 23 ), our findings align with recent research reporting that the addition of CTLA4 cytoplasmic tails to a 28z CAR led to increased cytotoxicity and reduced production of pro-inflammatory cytokines ( 7 ). Despite its previous association with enhancing T cell anti-tumor potential ( 21 ), the IL15RA cytoplasmic domain did not seem to provide impactful T cell co-stimulation amongst the variants.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…CTLA4, recognized as an inhibitory receptor on T cells, when embedded in the CAR signaling architecture resulted in potent CARs capable of promoting a robust T cell response, particularly amongst the CD4 compartment, with a persistent cytotoxic phenotype. Despite the inhibitory effect of CTLA4 signaling ( 23 ), our findings align with recent research reporting that the addition of CTLA4 cytoplasmic tails to a 28z CAR led to increased cytotoxicity and reduced production of pro-inflammatory cytokines ( 7 ). Despite its previous association with enhancing T cell anti-tumor potential ( 21 ), the IL15RA cytoplasmic domain did not seem to provide impactful T cell co-stimulation amongst the variants.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we included the signaling domains of CD40 (TNFRSF5) and the cytokine receptor chain IL15RA, which in preclinical studies have demonstrated the ability to enhance the anti-tumor properties of CARs ( 6 , 20 , 21 ). Lastly, CTLA4 was chosen as an example of an inhibitory receptor on T cells that still may enhance anti-tumor responses when incorporated into CARs ( 7 ). As a negative control, a non-signaling CAR (NS-CAR) was designed that lacks any intracellular signaling domains and is therefore unable to initiate CAR-dependent T cell activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To generate those cells, autologous or allogenic T cells are engineered with a TCR or CAR to recognize tumor‐specific antigen or tumor‐associated antigen and to active T cells for targeted lysis 63,64 . Traditionally, viral vectors such as lentivirus and retrovirus have been used to generate genetically engineered T‐cell products 65,66 . However, both lentivirus and retrovirus have limitations regarding their variable integration copy numbers, as well as the random genomic sites at which they integrate.…”
Section: Advancements Of Crispr Technology In T‐cell‐based Therapymentioning
confidence: 99%
“…63,64 Traditionally, viral vectors such as lentivirus and retrovirus have been used to generate genetically engineered T-cell products. 65,66 However, both lentivirus and retrovirus have limitations regarding their variable integration copy numbers, as well as the random genomic sites at which they integrate. This can cause variability in transgene expression and cell phenotypes due to insertional mutagenesis.…”
Section: Developing Multifunctional Gene Editing Systemsmentioning
confidence: 99%